Boosting Electrochemical CO2 Reduction on Metal–Organic Frameworks via Ligand Doping. Issue 12 (14th February 2019) - Dou, Shuo; Song, Jiajia; Xi, Shibo; Du, Yonghua; Wang, Jiong; Huang, Zhen‐Feng; Xu, Zhichuan J.; Wang, Xin
Abstract: Electrochemical CO2 reduction relies on the availability of highly efficient and selective catalysts. Herein, we report a general strategy to boost the activity of metal–organic frameworks (MOFs) towards CO2 reduction via ligand doping. A strong electron‐donating molecule of 1, 10‐phenanthroline was doped into Zn‐based MOFs of zeolitic imidazolate framework‐8 (ZIF‐8) as CO2 reduction electrocatalyst. Experimental and theoretical evidences reveal that the electron‐donating nature of phenanthroline enables a charge transfer, which induces adjacent active sites at the sp 2 C atoms in the imidazole ligand possessing more electrons, and facilitates the generation of *COOH, hence leading to improved activity and Faradaic efficiency towards CO production. Abstract : Organic doping : Electron‐donating 1, 10‐phenanthroline molecules are doped into ZIF‐8 to form a CO2 reduction electrocatalyst. The dopant enables charge transfer to the sp 2 C atom active site in the imidazole ligand and thus facilitates the generation of *COOH, hence leading to improved activity and Faradaic efficiency towards CO production.